The effects of long-term exposure to cadmium on the earthworm Eisenia Fetida (Oligochaeta) : an investigation of the development of genetic metal resistance - Voua otomo, Patricks (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2006.